Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis